2022
DOI: 10.4012/dmj.2021-287
|View full text |Cite
|
Sign up to set email alerts
|

Effect of bone defect width and a ferrule on the fracture characteristics of vertically fractured teeth reattached with adhesive resin cement: An <i>in vitro</i> study

Abstract: This study aimed to clarify the effects of vertical bone defect width and a ferrule on fracture of the fragments of fractured tooth reattached with adhesive resin cement (reattached tooth). The reattached tooth was built up by a fiber post and composite resin core for abutment and formed to the abutment with or without a ferrule. The vertical bone defect was fabricated with a V-shaped defect in different widths. The fracture load was evaluated using a universal testing machine. The vertical bone defect did not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Diana HH et al [56] in their study on 3D-FEA noted a significant increase in stress concentration in the apical third of radicular dentin during oblique force application, especially in the area opposite the loading point, attributed to the rigidity of the metal-ceramic crown and tooth bending. The study conducted by Kyogoku K et al [57] showed that the width of V-shaped defect did not affect the fracture load of rebonded teeth. However, the presence of ferrule increased the root fracture load.…”
Section: Discussionmentioning
confidence: 94%
“…Diana HH et al [56] in their study on 3D-FEA noted a significant increase in stress concentration in the apical third of radicular dentin during oblique force application, especially in the area opposite the loading point, attributed to the rigidity of the metal-ceramic crown and tooth bending. The study conducted by Kyogoku K et al [57] showed that the width of V-shaped defect did not affect the fracture load of rebonded teeth. However, the presence of ferrule increased the root fracture load.…”
Section: Discussionmentioning
confidence: 94%